Modified simplified method for isolation of lysostaphin from the culture filtrate of Staphylococcus staphylolyticus - Márová, I; Dadák, V (Folia microbiologica, 1993)
The present paper reports a modified method for isolation of lysostaphin--a bacteriolytic agent with specific affinity for staphylococcal cell wall. The proposed purification scheme includes three steps. The first procedure is ultrafiltration through a membrane filter giving a yield of 75.6%. The result of ultrafiltration is a concentrated, 10-times purified preparation of lysostaphin with specific activity 0.62 U/mg which can be used for digestion of S. aureus cells. Further step, performed by ion-exchange chromatography on DEAE-cellulose, yields a 60-times purified preparation containing a mixture of enzyme components of lysostaphin. The yield of this step is 47.2%, the preparation contains 3.54 U/mg protein. Using gel filtration on Sephadex G-50 a component with hexosaminidase activity was separated from the endopeptidase component on the basis of molar mass difference. A 270-times purified preparation of lysostaphin-endopeptidase with minimum of contaminating substances was obtained in this step. The yield of gel filtration was 22.1%, specific activity increased up to 16.3 U/mg protein.
Keywords: Carbohydrate Sequence; Culture Media; mikrobiologické techniky; kultivační média; gelová chromatografie; filtrace; Chromatography, Ion Exchange; Molecular Sequence Data; Chromatography, Gel; Filtration; sekvence aminokyselin; lysostafin; Lysostaphin; Staphylococcus; sacharidové sekvence; Microbiological Techniques; chromatografie iontoměničová; molekulární sekvence - údaje; Amino Acid Sequence